Dynamics of ecosystem service values in the Tarim River Basin - Sun, Mengxin; Shen, Xin; Xu, Hailiang; Shajiang·Aili, Ai (Frontiers in Environmental Science, 2025)
IntroductionUnderstanding spatial and temporal variations in ecosystem service values (ESV) and their driving factors is essential for effective management and decision-making. This study focuses on the Tarim River Basin, specifically the Aksu, Yarkant, Hotan, and Kaidu Peacock Rivers, and the mainstream Tarim River, which flow through key administrative regions.MethodsWe analyzed multi-temporal land use and land cover (LULC) data from 2000, 2005, 2010, 2015, and 2020, applying the comparable coefficient method to assess ESV changes and their spatial distribution. Geospatial analysis was used to identify the key drivers of ESV and their interactions.Results(1) The land use pattern in the study area has remained stable, with fluctuations driven by government policies and climate change. Farmland expanded by over 10% from 2000 to 2015, but its growth slowed between 2015 and 2020 due to the “Grain for Green” policy. Built-up areas grew significantly between 2005 and 2010 but declined afterward due to stricter urban planning. Glaciers have reduced in area, though their meltwater contributed to the increase in water bodies and wetlands. (2) ESV increased by 99.34 billion, with grasslands and water bodies contributing 60% and 10%, respectively. ESV peaked in 2015 due to wetland and water body expansion, but declined as wetlands shrank and glaciers retreated. (3) Key natural drivers of ESV include vegetation health (NDVI), proximity to water bodies, and precipitation, while socioeconomic factors like GDP have grown in influence. Interactions between climate and socioeconomic development complicate the dynamics of land use and ESV.DiscussionThe results indicate that while government policies and climate change significantly influence land use and ESV in the Tarim River Basin, socioeconomic factors are increasingly impactful. The complex interactions between climate and socioeconomic development have important implications for ecosystem management and decision-making. This highlights the need to consider both natural and socioeconomic drivers in land use planning and ecosystem service management.